How Can Clinicians Work Effectively With E-Mental Health Resources? - Robert King (Psychotherapy and Counselling Journal of Australia)
The purpose of this article is to stimulate thought among clinicians concerning the role of technology and in particular the Internet in provision of psychotherapy and counselling. The timing is influenced by the impending rollout of Commonwealth funded training for practitioners regarding the use of what will be called e-mental health (eMHPrac, 2014). I hope that this article will stimulate those readers not already familiar with the e-mental health services currently available to locate and explore one or more of these. Those readers who are already aware of e-mental health might find the discussion of how such resources can be utilized in routine practice helpful. I also hope that it will encourage practitioners to engage with training activities that will be available in the coming months and years.